The Division between Himalaya and Karakorum - Gansser, Augisto (Journal of Himalayan Earth Sciences, 1980)
The 5000 km long Peri-Indian Suture Zone has doubled in the western Himalaya and the northern branch forms the division between the Himalaya and the Karakoram. The northward directed Nanga Parbat-Haramosh crystalline spur controls structure and petrology of both the Suture Zones. It divides the over 2000 km long Transhimalayan batholith into the eastern Ladakh and the western Swat batholith. Geology and petrology of the Karakoram north of the Northern Suture Zone strongly contrast with the Himalaya to the south of it.